Using Gene Expression Analysis to Understand Complex Autoimmune Skin Disease Patients: A Series of Four Canine Cutaneous Lupus Erythematosus Cases - Amudzi, Alice A.; Piedra-Mora, Cesar; Ma, Diana Junyue; Wong, Neil B.; David, Clement N.; Robinson, Nicholas A.; Almela, Ramón M.; Richmond, Jillian M. (Frontiers in Veterinary Science, 2022)
Cutaneous Lupus Erythematosus (CLE) is an autoimmune skin disease that occurs in almost two-thirds of people with Systemic Lupus Erythematosus (SLE) and can exist as its own entity. Despite its negative impact on the quality of life of patients, lupus pathogenesis is not fully understood. In recent years, the role of gene expression analysis has become important in understanding cellular functions and disease causation within and across species. Interestingly, dogs also develop CLE, providing a spontaneous animal model of disease. Here, we present a targeted transcriptomic analysis of skin biopsies from a case series of four dogs with complex autoimmunity with suspected CLE. We identified 92 differentially expressed genes (DEGs), including type 1 interferon, B cell, and T cell-related genes, in the four cases compared to healthy skin margin controls. Additionally, we compared our results with existing CLE datasets from humans and mice and found that humans and canines share 49 DEGs, whereas humans and mice shared only 25 DEGs in our gene set. Immunohistochemistry of IFNG and CXCL10, two of the most highly upregulated inflammatory mediators, confirmed protein-level expression and revealed immune cells as the primary source of CXCL10 in dogs with SLE, whereas keratinocytes stained strongly for CXCL10 in dogs without SLE. We propose that gene expression analysis may aid the diagnosis of complex autoimmune skin diseases and that dogs may provide important insights into CLE and SLE pathogeneses, or more broadly, skin manifestations during systemic autoimmunity.